CBFβ-SMMHC inhibition triggers apoptosis by disrupting MYC chromatin dynamics in acute myeloid leukemia - Pulikkan, John Anto; Müller-Tidow, Carsten (Cell, 2018)
The fusion oncoprotein CBFβ-SMMHC, expressed in leukemia cases with chromosome 16 inversion, drives leukemia development and maintenance by altering the activity of the transcription factor RUNX1. Here, we demonstrate that CBFβ-SMMHC maintains cell viability by neutralizing RUNX1-mediated repression of MYC expression. Upon pharmacologic inhibition of the CBFβ-SMMHC/RUNX1 interaction, RUNX1 shows increased binding at three MYC distal enhancers, where it represses MYC expression by mediating the replacement of the SWI/SNF complex component BRG1 with the polycomb-repressive complex component RING1B, leading to apoptosis. Combining the CBFβ-SMMHC inhibitor with the BET inhibitor JQ1 eliminates inv(16) leukemia in human cells and a mouse model. Enhancer-interaction analysis indicated that the three enhancers are physically connected with the MYC promoter, and genome-editing analysis demonstrated that they are functionally implicated in deregulation of MYC expression. This study reveals a mechanism whereby CBFβ-SMMHC drives leukemia maintenance and suggests that inhibitors targeting chromatin activity may prove effective in inv(16) leukemia therapy.
corrected online: July 6, 2018
Gesehen am 15.05.2020